MODEL KKN SISDAMAS UIN SUNAN GUNUNG DJATI BANDUNG: TANTANGAN DAN PELUANG PELAKSANAAN - Fridayanti Fridayanti; Ramdhani Wahyu Sururie; Rohmanur Aziz; Wisnu Uriawan; Zulqiah Zulqiah; Yadi Mardiansyah (Al-Khidmat, 2019)
Sisdamas Community Service Program is a community service model developed by UIN Sunan Gunung Djati Bandung. This model is a form of Education-based service that involves collaboration between facilitators from the UIN Sunan Gunung Djati and the community. The model was developed as a framework for implementing Community Service Programs in assessing the situation and conditions of the community and developing work plans. The purpose of this article is to describe what and how Sisdamas Community Service Program and the challenges of implementing the model and future implementation opportunities